Implementation of BRIMO Superapps by the Millennial Generation for a Sustainable Economy - Darmawan, Ekwan; Indriani, Farida (Research Horizon, 2024)
This study aims to analyses the factors influencing the adoption and use of the Superapps BRIMO application by millennials at BRI Makassar Regional Unit and its impact on green value creation for economic sustainability towards Golden Indonesia 2045. The main problem addressed in this research is the low adoption rate of mobile banking applications among millennials and how this application can contribute to green value creation. The research method used is a qualitative approach with data collection techniques through in-depth interviews and participant observation. The collected data will be analyzed using thematic analysis to identify the main factors influencing adoption and use. This research is expected to provide significant contributions to the development of strategies for increasing the adoption of environmentally friendly banking technology that supports economic sustainability.